CURRENT THEORETICAL AND PRACTICAL ASPECTS REGARDING THE PROTECTION AND LIMITS OF THE RIGHT TO PROTECTION OF HEALTH - Oana ŞARAMET (International Journal of Legal and Social Order No. 1 (2021), 2021)
The right to the protection of their health is one of the fundamental rights of every human being, a right which considers both the individual’s right to health, but also one’s right to benefit from state measures taken to ensure public health and hygiene. As a consequence, the international community, but especially states, have the obligation to facilitate the accomplishment of this right, especially during times of pandemic, when we can consider, also on a legislative level, limitations in the exercise of this right. Through this article, we aim to identify the characteristics of this right in the present sanitary context, by making appreciations from the perspective of international and regional regulations, including the declarations and comments of some international bodies with duties in public health. We will also provide short appreciations in regard to national laws which are relevant given the connection to the respect of the right to the protection of health. Thus, we will point out the limitations of this right especially in regard to its exercise.
Keywords: health; solidarity; gradual steps; right-premise; right